Acid-Catalyzed Ring-Opening Isomerizations of Cyclopropenes - Phun, Lien H.; Aponte-Guzman, Joel; France, Stefan (Synlett, 2012)
Acid-catalyzed cyclopropene cycloisomerizations are discussed as a means to generate ring systems. Herein, the recent results obtained in our group are contrasted with previous examples in the literature. Particular emphasis is placed on the mode of activation which, for our case, results in a different ring-opening mechanism than previously observed. The potential of the method as a tool for organic chemists is demonstrated by the synthesis of a host of benzo-fused heteroaromatic and heterobiaryl products.
Keywords: cyclopropenes; annulations; Friedel–Crafts reaction; fused ring systems; arenes